Unraveling the Effects of the Financial Crisis on the Going Concern of Sri Lankan Tourism-Related SMEs: A Qualitative Inquiry - Lokeshwara, Anuja Akalanka; Wickramanayaka, Wickramanayakage Demini Avindya; Nilumind, Pradhana Mudiyanselage Disuri Ruwanya; Deepanayake, Kekanadura Vidana Arachchige Pumudu Chamathka; Wijayasundara, Thulani Pulara; Kumarapperuma, Chathurini (Centre For Tourism Planning and Development, 2024)
This research focuses on assessing the repercussions of the financial crisis on the sustainability of Sri Lankan tourism-related SMEs. Employing purposive sampling, twelve SME owners, each with a minimum of five years of operational history within the years 2018 to 2022, were selected to represent this vital sector. Through in-depth interviews, we investigate how the financial crisis affected the continued operation of these tourism-related SMEs. The findings demonstrate the diverse and profound impacts of the crisis. Many SMEs grappled with rising costs, inadequate working capital, and the looming threat of bankruptcy. Notably, the financial crisis marked a turning point for Sri Lanka's SMEs, triggering a shift in the domestic production landscape due to currency fluctuations and import constraints. The study also delves into the dynamic relationship between financial resources and organizational strategies, revealing configurations that ranged from notably productive to less so. We explore how increased financial resources, amidst macroeconomic restrictions, could influence these dynamics. In summary, this study provides critical insights into the unique challenges faced by tourism-related SMEs in Sri Lanka during the financial crisis. By implementing the recommended strategies, these enterprises can not only navigate the crisis's hurdles but also harness new growth opportunities.